2020
DOI: 10.3390/reports3010001
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D System in Humans and Mice: Similar but Not the Same

Abstract: Vitamin D is synthesized in the skin from 7-dehydrocholesterol subsequently to exposure to UVB radiation or is absorbed from the diet. Vitamin D undergoes enzymatic conversion to its active form, 1,25-dihydroxyvitamin D (1,25D), a ligand to the nuclear vitamin D receptor (VDR), which activates target gene expression. The best-known role of 1,25D is to maintain healthy bones by increasing the intestinal absorption and renal reuptake of calcium. Besides bone maintenance, 1,25D has many other functions, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Both mice and humans use UV-exposure as a 1,25(OH) 2 D 3 source, but as mice are nocturnal, they have less opportunity to expose themselves to UV light. Additionally, both humans and mice use their diet as a source of vitamin D (53). Mutations in the Vdr or Cyp27b1 genes in mice result in phenotypes similar to those seen in humans with these mutations (54-57).…”
Section: Circulating Fgf23 Regulators 125-dihydroxyvitamin Dmentioning
confidence: 99%
“…Both mice and humans use UV-exposure as a 1,25(OH) 2 D 3 source, but as mice are nocturnal, they have less opportunity to expose themselves to UV light. Additionally, both humans and mice use their diet as a source of vitamin D (53). Mutations in the Vdr or Cyp27b1 genes in mice result in phenotypes similar to those seen in humans with these mutations (54-57).…”
Section: Circulating Fgf23 Regulators 125-dihydroxyvitamin Dmentioning
confidence: 99%
“…Perhaps the effects of vitamin D deficiency on the timing of human tooth initiation are dose‐dependent, causing either acceleration or deceleration depending on the severity of vitamin D deficiency. Either way, while dietary vitamin D level may alter dental developmental timing in humans, our data suggest that mouse dental developmental timing is less sensitive to vitamin D. This difference between Mus and Homo may be explained by differences between their two vitamin D systems (Marcinkowska, 2020). In humans, VDR is regulated by liganded VDR as well as by other nuclear receptors and their ligands (Marcinkowska, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…In humans, VDR is regulated by liganded VDR as well as by other nuclear receptors and their ligands (Marcinkowska, 2020). Mouse VDR is autoregulated by the presence of liganded VDR only (Marcinkowska, 2020; Zella et al, 2006). However, many studies (e.g., Bouillon et al, 2008; Chun et al, 2019; Demay, 2013; Zhang et al, 2007) have shown that vitamin D deficiency affects the development of murine bones and teeth.…”
Section: Discussionmentioning
confidence: 99%
“…This VDR gene is located on chromosome number 12 in humans, 15 in mouse. It interacts with other related nuclear receptors such PPAR-γ, RXR-α, and LXR-α and thyroid hormone receptor (TR) [15], [16]. The molecular weight of this protein is approximately 50 kDa [17].…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%